Phylogenetic relationships in the Drosophila fasciola species subgroup (Diptera, Drosophilidae) inferred from partial sequences of the mitochondrial cytochrome oxidase subunit I (COI) gene - Erica C.C. Silva-Bernardi; Adriana C. Morales; Fabio M. Sene; Maura H. Manfrin (Genetics and Molecular Biology, 2006)
The repleta group is one of the largest and most complex species groups in the genus Drosophila, representing an important biological model for the elaboration of evolutionary and biogeographical hypotheses on the American Continent. It is divided into six subgroups, of which the fasciola subgroup is the only one with most of its species found in the humid forests of Central and South America. With the aim of understanding the origin and evolution of the fasciola subgroup, and consequently adding information about the repleta group, we analyzed partial sequences of the mitochondrial cytochrome oxidase subunit I (COI) gene of nine Drosophila species (D. carolinae, D. coroica, D. ellisoni, D. fascioloides, D. ivai, D. moju, D. onca, D. rosinae and D. senei). The phylogenetic hypotheses obtained neither defined the relationships between the subgroups of the repleta group nor defined all the interspecific relationships in the fasciola subgroup. We found that the species D. carolinae, D. coroica, D. onca, D. rosinae and D. senei comprised a clade in which D. carolinae, D. onca and D. senei appeared together at a polytomy while D. fascioloides and D. ellisoni comprised another clade with a high bootstrap value.